(untitled) (Italian Journal of Public Health, 2010)
Background: Violence in healthcare settings places nurses at risk for physical assaults (PA) and non-physical violence (NPV – threat, sexual harassment, verbal abuse). Studies on life-span violence suggest that persons with violence histories are more likely to experience future PA. Yet, little is known about the relation between violence history and risk of current violence among healthcare workers. The aim of the study was to investigate whether or not reported history of work-related and non-work-related PA and NPV was associated with the risk of current work-related PA among nurses. Methods: From a comprehensive survey of 6,300 randomly selected Minnesota nurses, a nested case control study (N= 310 cases and 944 controls) was conducted. Multivariate logistic regression analyses were used o estimate odds ratios (OR) and 95% confidence intervals (CI). Directed acyclic graphs identified potential onfounders. Horvitz-Thompson reweighting was applied to adjust for unknown eligibility and non-response. Results: Reported histories of work-related PA and work-related threat were associated with levated risks f current work-related PA (OR = 12.8; 95% CI = 2.2, 73.9 and OR = 4.8; CI = 1.1, 20.9, respectively). Risks ere elevated, but not important, for histories of work-related sexual harassment (OR = 1.8; CI = 0.5, 6.3) and verbal abuse (OR = 1.9; CI = 0.6, 5.7). History of non-work-related PA was not associated with current work-related PA, nor was history of non-work-related NPV. Conclusions: Results identified increased risks of current work-related violence among nurses who reported work-related violence histories. These results serve as a basis for targeted interventions and further research.